Causes of Early Girls’ Marriages in South Punjab: A Case Study of Rajanpur District - Aqeela Noor; Muhammad Safdar Tahir; Saira Ashraf; Nazia Siddique; Muhammad Farooq (Review Journal of Social Psychology & Social Works, 2024)
Early marriages, especially among girls, remain a critical issue in Pakistan, with rural regions such as Rajanpur in South Punjab being among the most affected. This research investigates the underlying causes of early girls’ marriages in Rajanpur, focusing on socio-economic, cultural, educational, and legal factors. By employing a quantitative research method by using questionnaire of five point Likert scales and collect 200 respondent data from rural and urban areas of district Rajanpur. The study examines how deep-rooted traditions, poverty, lack of education, and weak law enforcement contribute to the persistence of early marriages. Findings suggest that in Rajanpur, early marriages are driven largely by poverty, as families marry off daughters to reduce financial burdens, and by cultural norms that view early marriage as a means to preserve family honor. The lack of access to education for girls further exacerbates the problem, reinforcing gender inequalities and limiting future opportunities. Moreover, the failure to enforce existing child protection laws leaves many girls vulnerable. This paper concludes with recommendations for policy interventions, such as improving access to education, strengthening legal frameworks, and raising community awareness. The findings are aimed at informing policymakers and community leaders to develop targeted strategies that address the root causes of early marriages and support the empowerment of girls in the region.